Upregulation of CSNK1A1 induced by ITGB5 confers to hepatocellular carcinoma resistance to sorafenib in vivo by disrupting the EPS15/EGFR complex - Li Gu; Xin Jin; Huaiyuan Liang; Chong Yang; Yu Zhang (Elsevier, 2023)
Oral multitarget tyrosine kinase inhibitors (TKIs), such as sorafenib, which suppress tumor cell proliferation and tumor angiogenesis, have been approved to treat patients with hepatocellular carcinoma (HCC). Of note, only approximately 30% of patients can benefit from TKIs, and this population usually acquires drug resistance within 6 months. In this study, we intended to explore the mechanism associated with regulating the sensitivity of HCC to TKIs. We revealed that integrin subunit β 5 (ITGB5) is abnormally expressed in HCC and contributes to decreased the sensitivity of HCC to sorafenib. Mechanistically, unbiased mass spectrometry analysis using ITGB5 antibodies revealed that ITGB5 interacts with EPS15 to prevent the degradation of EGFR in HCC cells, which activates AKT-mTOR signaling and the MAPK pathway to reduce the sensitivity of HCC cells to sorafenib. In addition, mass spectrometry analysis showed that CSNK1A1 binds to ITGB5 in HCC cells. Further study indicated that ITGB5 increased the protein level of CSNK1A1 through the EGFR-AKT-mTOR pathway in HCC. Upregulated CSNK1A1 phosphorylates ITGB5 to enhance the interaction between ITGB5 and EPS15 and activate EGFR in HCC cells. Thus, we identified a positive feedback loop between ITGB5-EPS15-EGFR-CSNK1A1 in HCC cells. This finding provides a theoretical basis for the future development of therapeutic strategies to improve the anti-HCC efficacy of sorafenib.